2018
DOI: 10.5194/angeo-36-167-2018
|View full text |Cite
|
Sign up to set email alerts
|

Depth of origin of ocean-circulation-induced magnetic signals

Abstract: Abstract. As the world ocean moves through the ambient geomagnetic core field, electric currents are generated in the entire ocean basin. These oceanic electric currents induce weak magnetic signals that are principally observable outside of the ocean and allow inferences about large-scale oceanic transports of water, heat, and salinity. The ocean-induced magnetic field is an integral quantity and, to first order, it is proportional to depth-integrated and conductivity-weighted ocean currents. However, the spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Indeed, ocean tides may supply the most predictable naturally occurring, global‐scale electromagnetic field source on Earth and the predictable phase‐locked astronomical periodicity has been a key element allowing both the successful theoretical modeling of these fields as well as their extraction from satellite magnetic records (Sabaka et al, , ; Tyler et al, ). The study of ocean tidal electromagnetic fields and their use as a sounding source in oceanographic and geophysical studies is currently receiving much attention (Grayver et al, , ; Irrgang et al, , , , ; Sabaka et al, , ; Saynisch et al, , , ; Schnepf, , ; Tyler, ; Velimsky et al, ) due to the unprecedented geomagnetic field coverage coming from the ESA Swarm mission (e.g., Friis‐Christensen et al, ) consisting of three satellites launched in 2013 and expected to continue until 2030.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, ocean tides may supply the most predictable naturally occurring, global‐scale electromagnetic field source on Earth and the predictable phase‐locked astronomical periodicity has been a key element allowing both the successful theoretical modeling of these fields as well as their extraction from satellite magnetic records (Sabaka et al, , ; Tyler et al, ). The study of ocean tidal electromagnetic fields and their use as a sounding source in oceanographic and geophysical studies is currently receiving much attention (Grayver et al, , ; Irrgang et al, , , , ; Sabaka et al, , ; Saynisch et al, , , ; Schnepf, , ; Tyler, ; Velimsky et al, ) due to the unprecedented geomagnetic field coverage coming from the ESA Swarm mission (e.g., Friis‐Christensen et al, ) consisting of three satellites launched in 2013 and expected to continue until 2030.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study of ocean climatology data (Tyler et al, ) suggests that over much of the global ocean, observed conductivity tracks observed temperature and over much of the remainder of the ocean, observed conductivity tracks observed salinity. However, time variations and depth integrals (e.g., Irrgang et al, ; Saynisch et al, ) combined with the nonlinearity of the equation for conductivity complicates the question of whether a linear relationship holds between conductance and OHC. Because of aliasing and sparse sampling of some regions of the ocean, it is possible that the relationship between conductance and OHC is not simply linear.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the signal strength at satellite altitude, the signal is approximately 30 % stronger at sea level. Additionally, substantial research has already investigated the relationship between oceanic-induced magnetic field variations, especially their radial component, and their oceanic causes (Saynisch et al, 2016Irrgang et al, 2016aIrrgang et al, , 2017Irrgang et al, , 2018. We add to this canon by investigating the impact of ENSO, the biggest interannual climate signal, on the oceanic tidally induced radial magnetic field.…”
Section: Oceanic Tidally Induced Currents and Emotssmentioning
confidence: 99%
“…Hz (Jager et al, 2010) are able to resolve the global structure of the oceanic tidally induced radial magnetic field. To be able to observe the presented variations an increase magnetometer precision of several orders of magnitude down to the femtotesla scale is necessary.…”
mentioning
confidence: 99%
“…Hz (Jager et al, 2010) magnetic field. To be able to observe the presented variations an increase magnetometer precision of several orders of magnitude down to the femtotesla scale is necessary.…”
Section: Comparison Of Derived Enso Indicesmentioning
confidence: 99%